2016
DOI: 10.1002/fes3.99
|View full text |Cite
|
Sign up to set email alerts
|

Feeding 11 billion on 0.5 billion hectare of area under cereal crops

Abstract: Despite impressive increase in global grain production since 1960s, there are 795 million food‐insecure and ~2 billion people prone to malnutrition. Further, global population of 7.4 billion in 2016 is projected to increase to 9.7 billion by 2050, with almost all increase occurring in developing countries. Thus, it is recommended that global food production be increased by 60 to 70% between 2005 and 2050. Global crop production increased threefold between 1965 and 2015 with a net increase of only 67 million ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 64 publications
0
64
0
3
Order By: Relevance
“…The goal is to produce more per unit area of land, fertilizers and pesticides, irrigation, energy, and emission of greenhouse gases. With this strategy, the land area needed for cereal production can be decreased rather than increased (Lal 2016a).…”
Section: Eco-intensification and Conservation Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The goal is to produce more per unit area of land, fertilizers and pesticides, irrigation, energy, and emission of greenhouse gases. With this strategy, the land area needed for cereal production can be decreased rather than increased (Lal 2016a).…”
Section: Eco-intensification and Conservation Agriculturementioning
confidence: 99%
“…However, such an indiscriminate intensification through plowing, flood-based irrigation, and high inputs of chemicals has strong adverse effects on the quality and functionality of soil, water, air, vegetation, and biodiversity (Benson 2014). Despite these massive inputs, agronomic production of food staples has stagnated in some regions (Grassini et al 2013), and new approaches to food production must be identified in the face of climate change (Beddington et al 2012;Foley et al 2011;Lal 2016aLal , 2018. Thus, the use of nutrients and pesticides, as well as rates and mode of application, in agroecosystems must be revisited (Drinkwater and Snapp 2007).…”
mentioning
confidence: 99%
“…Both reviews highlight the prominence of a productivist lens, in other words, SI aims to increase agricultural production in order to feed a rapidly growing global population. This productivist lens, often described in combination with a desire to increase food security, is noticeable in scientific reports and journal articles, as well as in policy documents released in the last decade (Elliott & Firbank, ; Foresight ; Franks, ; Garnett et al., ; Lal, ; The Royal Society ; Tilman, Balzer, Hill, & Befort, ). Major policy initiatives, such as Defra's Sustainable Intensification Research Platform (http://www.siplatform.org.uk), and a wider Sustainable Intensification Research Network (https://sirn.org.uk) funded by the Biotechnology and Biological Sciences Research Council, have recently explored the potential for SI in the UK and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…However in many cases, degraded land has marginal potential for production, even after costly rehabilitation. Lal (Lal 2016) suggested that agriculturally marginal and degraded soils should be avoided for this purpose (and could be set-aside for nature), and that lands with potential for higher yields could be restored, for example those in areas of sub-Saharan Africa and South Asia where there is potential for tripling or quadrupling of yields. Over 1.3 billion people however, use degraded agricultural land, particularly in the drylands (UNCCD 2017), and in general larger soil C sequestration rates can be achieved from interventions to increase C sequestration in degraded soils than from other soils (Minasny et al 2017).…”
Section: Practical Local Solutionsmentioning
confidence: 99%
“…There are a number of GHG mitigating practices which can be implemented to restore degraded and marginal land, such as the use of cover crops, avoiding overgrazing, using crop residues and organic composts and agroforestry, however employing these is not always straightforward (Paustian et al 2016). The conditions under which yields in sub-Saharan Africa and South Asia could be increased while sparing land should be investigated, utilizing the existing body of evidence on successful CSA interventions (FAO 2013) (see for example also (Sa et al 2017;van Noordwijk et al 2016;Soliman et al 2016;Lal 2016)) . The dichotomy between forest and agriculture itself may prevent the emergence of optimal solutions, as for example in a landscape where fodder for dairy cows can be derived from any part of the landscape (Lusiana et al 2012).…”
Section: Practical Local Solutionsmentioning
confidence: 99%